2015
DOI: 10.7314/apjcp.2015.16.8.3371
|View full text |Cite
|
Sign up to set email alerts
|

Purple Rice Bran Extract Attenuates the Aflatoxin B1-Induced Initiation Stage of Hepatocarcinogenesis by Alteration of Xenobiotic Metabolizing Enzymes

Abstract: Pigmented rice bran has been suggested to be a valuable source of beneficial phytochemicals. We investigated genotoxic and anti-genotoxic effects of purple rice bran extract (PRBE) in rats using a liver micronucleus assay. Purple rice bran was extracted with methanol, obtaining large amounts of phenolic compounds, including anthocyanins and small amounts of gamma-oryzanol. The experimental protocols were divided into two sets. Male rats were divided into three groups. Group 1 was a negative control, while Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The mechanistic basis of this effect has been found to be varietydependent, reflecting differences in the spectrum of bioactive compounds present in each rice variety (Baek et al, 2015). The high anthocyanin content of purple rice has been associated with an inhibitory effect on the growth of human hepatocellular carcinoma cells (Banjerdpongchai et al, 2013), while extracts of purple rice bran were able to block the first stage of aflatoxin B1-initiated hepatocarcinogenesis by inhibiting key metabolic activating enzymes (Suwannakul et al, 2015). Extracts of red rice have been shown to limit the invasiveness of cancer cells in a dose-dependent manner (Pintha et al, 2014).…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…The mechanistic basis of this effect has been found to be varietydependent, reflecting differences in the spectrum of bioactive compounds present in each rice variety (Baek et al, 2015). The high anthocyanin content of purple rice has been associated with an inhibitory effect on the growth of human hepatocellular carcinoma cells (Banjerdpongchai et al, 2013), while extracts of purple rice bran were able to block the first stage of aflatoxin B1-initiated hepatocarcinogenesis by inhibiting key metabolic activating enzymes (Suwannakul et al, 2015). Extracts of red rice have been shown to limit the invasiveness of cancer cells in a dose-dependent manner (Pintha et al, 2014).…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Although white rice is predominantly consumed, pigmented rice is an alternative food known for its health-promoting effects 8. Our group found that purple rice bran extract exhibited antigenotoxic effects on aflatoxin B 1 (AFB 1 )-induced micronucleus formation in rat liver by alteration of several xenobiotic metabolizing enzymes in AFB 1 metabolism 9. A number of varieties of rice and their potential beneficial effects have been investigated 10.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the extracts could not only inhibit the expression of CYP1A2 and CYP3A, but also increase the expression of GST and UGT which encouraged AFB 1 excretion. Further in in vivo studies, the genotoxicity was evaluated by micronucleus assay, and the result showed lower micronucleus formation in extractpretreated group than AFB 1 treated alone, confirming the capability of purple rice bran extract on the prevention of AFB 1 -induced genotoxicity [39].…”
Section: Purple Ricementioning
confidence: 74%